2015
DOI: 10.5185/amlett.2015.5817
|View full text |Cite
|
Sign up to set email alerts
|

 Effect Of Nanoclay On The Toughness Of Epoxy And Mechanical, Impact Properties Of E-glass-epoxy Composites

Abstract: Organically modified montimorillonite nanoclay was added to the epoxy and E-glass-epoxy composites. The influence of nanoclay content (varied between 0 to 5wt %) on the relative crosslink density and the fracture toughness of the epoxy matrix was studied. Differential scanning calorimetry (DSC) indicated that the amino functional groups present on the nanoclay react with the epoxy matrix to increase the crosslink density of about 13 and 18% at 3 and 5wt% addition, respectively. The toughness of the epoxy compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 24 publications
2
23
0
1
Order By: Relevance
“…Surface modified nanoclay addition leads to an increase in cross-linking density of epoxy, giving rise to increased toughness and tensile properties of the epoxy as a result of the load transfer interaction from the matrix to reinforcement [23]. The higher aspect ratio of nanoclay might have enhanced the tensile strength of the polymer matrix by enhancing the nanoclay interaction surface vicinity [24,25]. Nanoclay serves as an active stress transfer constituent in the ENCs, leading to plastic deformation in the epoxy and eventually increasing the tensile strength [4].…”
Section: Resultsmentioning
confidence: 99%
“…Surface modified nanoclay addition leads to an increase in cross-linking density of epoxy, giving rise to increased toughness and tensile properties of the epoxy as a result of the load transfer interaction from the matrix to reinforcement [23]. The higher aspect ratio of nanoclay might have enhanced the tensile strength of the polymer matrix by enhancing the nanoclay interaction surface vicinity [24,25]. Nanoclay serves as an active stress transfer constituent in the ENCs, leading to plastic deformation in the epoxy and eventually increasing the tensile strength [4].…”
Section: Resultsmentioning
confidence: 99%
“…This significantly explains the distinguishable characteristic of the nanoclay filler which has a high specific area imparts substantial improvements, even when present in small amounts. An investigation on the flexural strength of nanoclay‐E‐glass‐epoxy composites found the highest strength when incorporated with only 3 wt% of nanoclay loading . However, the addition of a higher amount of nanoclay filler up to 5 wt% gradually reduced the composites' strength because of the agglomerations that occurred at the higher nanoclay ratio, causing the embrittlement of the matrix.…”
Section: Resultsmentioning
confidence: 99%
“…This suggested that, at the 5 wt% nanoclay content, the composites absorbed more work of fracture and consequently showed higher mechanical resistance. Several studies have proved that, with the addition of nanofiller to a composite, the crack propagation induced by any test was forced to follow a tortuous path . As a result, the nanocomposites showed better resistance to the applied force, describing tougher behavior, compared to the pristine one.…”
Section: Resultsmentioning
confidence: 99%
“…Significant enhancement in fracture toughness of the matrix system was observed in various cases through key toughening mechanisms like crack pinning, crack deflection, crack bridging, and filler debonding [7,8]. Researchers endeavored to use nanofillers, like single-walled carbon nanotubes (SWCNT), double- walled carbon nanotubes (DWCNT), multi-walled carbon nanotubes (MWCNT) [9,10,11,12], graphene [13,14,15], nanoclay [16,17,18], and nanosilica [19,20,21] into various polymers and reported the effect of reinforcement in polymer composites. However, reinforcing nanofillers into the polymer matrix does not always enhance the fracture toughness and modulus of the composite material.…”
Section: Introductionmentioning
confidence: 99%
“…Johnsen et al [21] investigated the influence of nanofillers of different sizes as toughening agents and also explored the associated toughening mechanisms. Krushnamurthy et al [18] investigated the effect of nanoclay on the toughness behavior of E-glass composite laminates. It was noted that the toughness of the epoxy composite laminates increased by 25% at 3 wt% of nanoclay.…”
Section: Introductionmentioning
confidence: 99%